2016
DOI: 10.1111/bju.13610
|View full text |Cite
|
Sign up to set email alerts
|

The Australian laparoscopic non robotic radical prostatectomy experience – analysis of 2943 cases (USANZ supplement)

Abstract: The Australian experience of Fellowship trained surgeons performing LRP demonstrates favourable peri-operative, oncological and functional outcomes in comparison to published data for open, laparoscopic and robotic assisted radical prostatectomy. In our Australian centres, LRP remains an acceptable minimally invasive surgical treatment for prostate cancer despite the increasing use of robotic assisted surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…One such custodian for urologists is the BJU International journal which centralises quality evidence-based urological knowledge. For example, this journal has key papers in the myriad of localised and systemic [13] treatment of prostate cancer, such as active surveillance [14], robotic prostatectomy [15], brachytherapy [16], and even alternative treatments like phytotherapy [17]. In the same way, reputable organisations can summarise evidence-based knowledge into a centralised online library in simple language so that our patients do not have to sift through the ocean of unsorted information on the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…One such custodian for urologists is the BJU International journal which centralises quality evidence-based urological knowledge. For example, this journal has key papers in the myriad of localised and systemic [13] treatment of prostate cancer, such as active surveillance [14], robotic prostatectomy [15], brachytherapy [16], and even alternative treatments like phytotherapy [17]. In the same way, reputable organisations can summarise evidence-based knowledge into a centralised online library in simple language so that our patients do not have to sift through the ocean of unsorted information on the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…We wished to describe the local learning curve in Australia for Fellowship‐trained LRP surgeons, by examining a subset of a larger Australian LRP series …”
Section: Discussionmentioning
confidence: 99%
“…Potency and continence rates are not addressed in this study because not all contributing surgeons had data, although limited results are reported in the descriptive publication of this series …”
Section: Discussionmentioning
confidence: 99%
“…One argument of the advocates of RARP is the reduced length of hospitalization and therefore improved quality of life for the patient [ 8 ]. However, there are also other studies that show similar perioperative, oncological, and functional outcomes for laparoscopic RP compared to open and robotic RP if surgeons were high volume surgeons [ 17 ].…”
Section: Discussionmentioning
confidence: 99%